Antinematicidal Potency of Arum maculatum L. (Araceae) to Control Macrocyclic Lactone Derivative-Resistant Gastrointestinal Roundworms in Ovine - Kareem Khoshnow Hamad (Zanco Journal of Pure and Applied Sciences, 2020)
Antinematicidal resistance has been emerging between the gastrointestinal (GI) nematode populations in ovine to the popular broad-spectrum artificial drugs [say macrocyclic lactone (ML) derivatives] in most countries of the world including Kurdistan region of Iraq. Hence, the present study was designed to evaluate the efficacy of crude aqueous ethanol extract (CAEE) of native Arum (A.) maculatum L. (common name: snakehead) in eliminating ML derivative-resistant GI roundworms in ovine. The study was conducted on private sheep farms in Qushtapa district, Erbil governorate from October 2018 to March 2019. After confirmation of infestation with various GI nematodes (Nematodirus 37%, Marshallagia 42% and Trichuris 21%), the tentative animals were divided into six groups (n=15). One group was allotted for diagnosis of resistance against ML and one group for control. The faecal egg count reduction test (FECRT) has revealed the rampancy of resistance to the aforementioned antiparasitic. According to the RESO Computer Program, the calculated FECR% and lower confidence interval 95% were 69.83% and 48.4% respectively. For antiparasitic evaluation of the above phytomedicine, four groups (n=15) were exploited. The FECR% results post-therapy with 25, 50, 75, and 100 mg kg-1 BW of the A. maculatum CAEE were 21.13, 54.91, 73.28 and 96.27 respectively. According to these data and related references, the dose; 100 mg kg-1 BW was deemed effective, whilst other doses were ineffective. The ovicidal activity of the medicinal herb was also tested in vitro via executing egg hatch assay. The calculated LC50 value was 2.551μg ml-1 (range 2.454-2.647) after conduction of the assay. Having said, the same control group was employed because statistically, all the groups were belonged to the same population.